Understanding the ‘Look but Fail to See’ Error - Robbins, Chloe J. (2019)
Collisions at intersections, which involve a car driver pulling out into the path of another road user (often a motorcycle), have generally been attributed to a failure in the driver’s visual search. These incidents have thus been described as being the result of ‘look but fail to see’ (LBFTS) errors. This explanation suggests that although the car driver directs their attention towards the approaching vehicle, they do not form a representation of this vehicle, indicating a perceptual error. Previous theoretical frameworks used to understand these crashes have focussed on attentional and perceptual explanations, as well as the possible influence of top-down and bottom-up factors on drivers’ behaviour. While the investigation of the influence of top-down factors, such as experience and attitudes, has been continued in the current thesis by examining how these factors may affect drivers’ behaviour at junctions, the thesis also considers other potential explanations for the LBFTS error, by breaking down the previous framework into specific testable stages. The structure of the thesis and the theoretical basis for it is described in an extended introduction which is followed by six specific papers presented in the format in which they have been published or submitted for publication.